The Arabs in the Chronicle of Constantine Manasses - Leszka, Mirosław J. (Studia Ceranea, 2019)
This paper looks into the piece by Constantine Manasses considering how it depicts the Arabs. It appears Manasses saw the Arabs primarily as bloody and cruel plunderers who invaded the Byzantine lands. Indeed, they won some of the fights against the Byzantines but eventually had to accept their superiority and concede defeat. It should also be noted that Constantine Manasses did not bring up religious themes when referring to the Arabs.